Kids Can Draw: Animals of the World, A Child's First Drawing Book - Legendre, Philippe (Laguana Hills, CA : Walter Foster Publishing Inc, 1994)
A child's first drawing book.
Keywords: Drawing; Animals; Drawing and drawings